1977
DOI: 10.1192/bjp.130.5.452
|View full text |Cite
|
Sign up to set email alerts
|

On the Prevalence, Diagnosis and Management of Lithium-Induced Hypothyroidism in Psychiatric Patients

Abstract: Fifty-three psychiatric patients who had been receiving treatment with lithium continuously for more than two years were examined to estimate the prevalence of lithium-induced hypothyroidism. It was found to be 20 per cent among women. No men were affected among these patients. In order to study the characteristics of the disorder further cases were drawn from another population. One third of the patients developed hypothyroidism during their first year of treatment, others not until after 9 years. About two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…Cross-sectional studies of lithium-induced goitre reveal a prevalence of 0 to 60% [51]; prevalence estimates are much higher (30–59%) when more sensitive ultrasonographic scans are used to detect increases in thyroid volumes [32, 87, 90]. Several studies of patients on lithium have found an elevated rate of anti-thyroid antibodies, ranging from about 8 to 49% in such patients; these rates were significantly higher than those among control patients or the general population [84, 89, 91100]. An almost equal number of studies have failed to find an association between elevated antibody titres and exposure to lithium [32, 53, 73, 74, 101–104].…”
Section: Lithium and Hpt Axis Dysfunctionmentioning
confidence: 99%
“…Cross-sectional studies of lithium-induced goitre reveal a prevalence of 0 to 60% [51]; prevalence estimates are much higher (30–59%) when more sensitive ultrasonographic scans are used to detect increases in thyroid volumes [32, 87, 90]. Several studies of patients on lithium have found an elevated rate of anti-thyroid antibodies, ranging from about 8 to 49% in such patients; these rates were significantly higher than those among control patients or the general population [84, 89, 91100]. An almost equal number of studies have failed to find an association between elevated antibody titres and exposure to lithium [32, 53, 73, 74, 101–104].…”
Section: Lithium and Hpt Axis Dysfunctionmentioning
confidence: 99%
“…Psychiatric patients on lithium (Li) therapy frequently develop goiter and/or hypothyroidism [1], These effects are commonly ascribed to the antithyroid activity of Li [2], but the possibility that this drug might trigger thyroid autoimmunity has also been suggested [3][4][5], However, the data supporting the latter hypothesis are scanty and contradictory; the prevalence of circulating antithyroid autoantibodies in patients on long-term Li therapy ranges from 14 to 50% in different investigations [6][7][8][9] and no conclusive data may be derived from the few longitudinal studies presently available [9][10][11][12], Differences in individ ual sensibility related to genetic heterogeneity and/or to underlying subclinical thyroid disease might explain the above discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…An increased prevalence of hypothyroid ism (15-25%, depending on the mode of classification) [60], in some cases accompa nied by a compensatory goiter, is well estab lished among long-term lithium patients [67], Biochemical changes, e.g. increased se rum thyrotropin (TSH), as well as goiter with or without biochemical hypothyroidism, re spond to adequate substitution treatment with thyroid hormones, but an internist should be consulted before institution of such treatment [59,66].…”
Section: Lithium In Endocrinologymentioning
confidence: 99%